Analisa Karakteristik Perjalanan Penumpang Angkutan Udara Dan Analisa Kebutuhan Parkir Di Bandara Sultan Syarif Kasim II Pekanbaru - Muhammad Reza Satria; Yosi Alwinda (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
The improvement of  passenger count in Sultan Syarif Kasim II Airport makes the activity in the airport is rising up, so an appropriate parking facility is required and compatible with parking demand. In analyzing of parking demand in Sultan Syarif Kasim II Airport, it necessary to know the existing parking characteristic. From the result of  parking characteristic analysis that is parking accumulation, the parking demand can be determined. By using maximum parking accumulation method, obtained the maximum parking accumulation 277 cars at 12.4613.00 Wib and 267 motorcycles at 14.31-14.45Wib on first day of survey, on second day 416 cars at 17.16-17.30Wib and 289 motorcycles at 14.31-14.45 Wib and on third day 369 cars at 17.0117.15 Wib and 291 motorcycles at 14.31-14.45 Wib. Parking duration in this airport is dominated by 0-30 minutes of duration for car and motorcycle in whole survey day. This parking duration classified to short-term parking because under 2 hours of parking duration,  while parking indeks on the first day of survey 87,11% for car and 142,87% for motorcycle, on the second day 130,82% for car and 154,55% for motorcycle and on third day 116,40% for car and 155,61% for motorcycle. The maximum of parking demand identified 416 parking lot for car  and 291 parking lot for motorcycle in  2013. In addition, interview survey to the passengers held with parking survey in the same time to know how the characteristics of passenger trip in Sultan Syarif Kasim II international airport. The result of the passenger survey will be displayed in percentage in pie diagram.    Keywords: parking, Airport, Characteristic of parking, parking demand,